Resource partitioning in a ladybird, Menochilus sexmaculatus: function of body size and prey density. Issue 1 (3rd December 2014) - Chaudhary, D.D.; Kumar, B.; Mishra, G.; Omkar
Abstract In the present study, resource partitioning by natural conspecific size variants (small and large) of ladybird, Menochilus sexmaculatus (Fabricius) females, in response to varying prey densities was assessed using functional and numerical responses as measures of prey density. The prey provided was small (second) and large (fourth) instars of Aphis craccivora Koch. Results revealed that under choice condition, small and large females of M. sexmaculatus consumed higher number of small and large instars, respectively. Small females exhibited a modified Type II functional response on small aphid instars and a Type II functional response on fourth aphid instars. Large females exhibited a Type II functional response when provided either second or fourth aphid instars. Numerical response in terms of numbers of eggs laid by both the females increased with increase in the density of either of the aphid instars. However, in small females, oviposition had a positive correlation with the numbers of small and large aphid instars consumed; being strong for the small aphid instars. While in large females, oviposition was positively correlated with the numbers of large aphid instars consumed and not small aphid instars. It therefore seems that intraspecific resource partitioning in M. sexmaculatus occurs prominently in large females than the small females.